Asnaf satisfaction on zakat management at UiTM Shah Alam / Mohammad Salmie Mohd Zaidi - Mohd Zaidi, Mohammad Salmie (2018)
This study was conducted to examine the level of student satisfaction on zakat management at Pusat Zakat UiTM Shah Alam. The sample was chosen randomly, involving 107 students receiving zakat assistance. The data were collected using a questionnaire instrument and analyzed using SPSS software. The result of the analysis of the research data shows that the level of student satisfaction towards zakat management at Pusat Zakat UiTM Shah Alam is satisfying with a mean score of 4.2579 for satisfaction on human resources services, 4.1271 for satisfaction on management on zakat distribution and 4.0049 for satisfaction on zakat aid rate. The finding of this study is also expected to be a guide to Pusat Zakat UiTM Shah Alam to improve their zakat management.